Application of Inclinometer in Arch Bridge Dynamic Deflection Measurement - Xianlong He; Xueshan Yang; Lizhen Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Dynamic deflection measurement is an important component to the bridge loading experiment or health monitoring. Using high-precision inclinometers to test the dynamic deflection is a good method for High-Speed Railway Bridge deflection measurement in this paper, we develop a kind of precision inclinometer which comprehensives the Capacitive sensor technology and the Servo sensor technology and has been called QY inclinometer. We also derive a new theory to calculate deflection based on inclination. Using eleven QY inclinometers and three Cable-Displacement sensors, we have done a comparison dynamic deflection measurement experiment on an arch bridge. Test results indicate: using inclinometers to measure dynamic deflection can achieve the same accuracy with Cable-Displacement sensor which can achieve 0.1 mm accuracy. Therefore, this experiment has proved Using high-precision inclinometers to measure dynamic deflection of bridge can satisfy the dynamic deflection measurement request of high-speed railway bridge. Comparing with other methods of dynamic deflection measurement, using high-precision inclinometers to measure dynamic deflection is very easy to operate, and also do not need find a static reference point. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4933